2008
DOI: 10.3892/ijo.33.1.169
|View full text |Cite
|
Sign up to set email alerts
|

CD31 density is a novel risk factor for patients with B-cell chronic lymphocytic leukaemia

Abstract: CD31 is the physiological ligand for CD38. CD38 expression in a high percentage of malignant cells is a risk factor for patients with B-cell chronic lymphocytic leukaemia (B-CLL). A previous investigation demonstrated that quantification of CD38 improves upon the prognostic value of the percentage expression. A recent study states that the percentage of CD31 expression is not predictive in B-CLL. We reassessed the predictive power of CD31 in a cohort of 120 patients with B-CLL. Peripheral blood cells were stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Expression of CD38 is a negative prognostic marker in chronic lymphocytic leukemia (CLL) and is associated with short survival and relative lack of IgVH mutation, but the relationship is not absolute (47–51). Although, discussing the role of CD38 in CLL and other lymphomas is beyond the scope of this review, the description of its interaction with CD31 can give us some light in how CD38 is participating in cell activation and survival.…”
Section: Cd38 Ligandmentioning
confidence: 99%
“…Expression of CD38 is a negative prognostic marker in chronic lymphocytic leukemia (CLL) and is associated with short survival and relative lack of IgVH mutation, but the relationship is not absolute (47–51). Although, discussing the role of CD38 in CLL and other lymphomas is beyond the scope of this review, the description of its interaction with CD31 can give us some light in how CD38 is participating in cell activation and survival.…”
Section: Cd38 Ligandmentioning
confidence: 99%
“…CD31 is an adhesion molecule that participates in cellular interactions [ 50 , 51 ] and is a ligand for CD38 [ 52 ]. Their interaction has been associated with the microenvironment of leukemia cells [ 53 55 ] and high CD31 density has been associated to B cell chronic lymphocytic leukemia [ 56 ]. On the other hand, CD39 is an integral membrane protein, whose main role is to metabolize extracellular ATP and ADP into AMP [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Because expression of CD38 correlates with poor prognosis in B-cell chronic lymphocytic leukemia (B-CLL), 8 clinical implication of its natural ligand, CD31, 9 has also been investigated 10 and showed that expression of CD31 further defines a sub-group of disease 11 and low expression of this marker is an adverse prognostic factor. 12 Anti-CD31 mouse monoclonal antibodies (MAbs) and their derivatives chimeric and humanized MAbs, therefore could be useful tools in diagnosis, research and therapy of diseases. Production of MAbs by hybridoma technology was first introduced by George Kohler and Cesar Milestain.…”
Section: Introductionmentioning
confidence: 99%